La simbolica dello straniero nel Salterio - Bazyliński, Stanisław (The Biblical Annals, 2024)
Who is a foreigner in the Hebrew Psalter? The article answers this question in two sections. First, seven terms referring to “foreigner” are examined to determine their individual characteristicsin the Psalms and their correspondence to biblical texts outside the Psalter. Second, other literary motifs are analyzed in a cursory reading of Psalms 105, 106 and 137. The Psalter outlines a partial picture of the foreigner, which is subordinated to theological and symbolic issues. The Psalms primarily recall the adventures of Israel, which had to frequently change its place of residence for various reasons. As a foreigner, deprived of land and permanent residence, he experienced the ups and downs of migrant life and ultimately strove to integrate into a new socio-cultural environment. Defending one’s identity and maintaining national and religious integrity is portrayed as a difficult process, at risk. Another type of foreigner in the Psalms is the non-Jew, individually or communally, who enjoys the social and legal protection to which the poor are entitled. Either he is a well-integrated member of society, or he remains unassimilated. In the latter case, his false words, harmful actions and physical hostility toward Israel come to the fore. Finally, in the Book of Psalms, terms associated with “foreigner” are part of figurative language. The vocabulary sometimes either evokes non-literal associations with foreign countries, nations and foreign gods, or denotes an emotional state of suffering and isolation. Moreover, key lexemes symbolize the transitory human condition, emphasizing the marginalization and even segregation of the petitioner from the household.